Analisis Pengangguran Terdidik di Indonesia - Vini Alvio Neti; Sari, Yollit Permata (Media Riset Ekonomi Pembangunan (MedREP), 2024)
This study aims to determine and analyze Educated Unemployment in Indonesia. The data used is secondary data from 2013 to 2022 with a sample of 33 provinces in Indonesia obtained from the Central Statistics Agency (BPS) and the Investment Coordinating Board (BPKM). This study uses panel data regression analysis with the best model chosen is the Fixed Effect Model (FEM). The results found that: (1) Provincial Minimum Wage has a positive and significant effect on the number of educated unemployed in Indonesia, (2) Economic Growth has a negative and signific ant effect on the number of educated unemployed in Indonesia, (3) Foreign Direct Investment has a negative and insignificant effect on the number of educated unemployed in Indonesia and (4) Covid-19 Dummy Variable shows that during Covid-19 the increase in the number of educated unemployed in Indonesia is not significant compared to before Covid-19 occured. Based on the research, it is recommended for the government to protect labor by setting a minimum wage without ignoring the company's ability and the government is expected to create a labor-intensive investment climate.